Resident Experiences With a Place-Based Collaboration to Address Health and Social Inequities: A Survey of Visitors to the East Harlem Neighborhood Health Action Center - Rachel Dannefer MPH, MIA; Luke Sleiter MPH; Jessie Lopez BS; Jaime Gutierrez MPH; Carl Letamendi PhD, MBA; Padmore John MS; Zinzi Bailey ScD, MSPH (SAGE Publishing, 2022)
In 2016 and 2017, the New York City Department of Health and Mental Hygiene established Neighborhood Health Action Centers (Action Centers) in disinvested communities of color as part of a place-based model to advance health equity. This model includes co-located partners, a referral and linkage system, and community space and programming. In 2018, we surveyed visitors to the East Harlem Action Center to provide a more comprehensive understanding of visitors' experiences. The survey was administered in English, Spanish, and Mandarin. Respondents were racially diverse and predominantly residents of East Harlem. The majority had been to the East Harlem Action Center previously. Most agreed that the main service provider for their visit made them feel comfortable, treated them with respect, spoke in a way that was easy to understand, and that they received the highest quality of service. A little more than half of returning visitors reported engaging with more than one Action Center program in the last 6 months. Twenty-one percent of respondents reported receiving at least one referral at the Action Center. Two thirds were aware that the Action Center offered a number of programs and services and half were aware that referrals were available. Additional visits to the Action Center were associated with increased likelihood of engaging with more than one program and awareness of the availability of programs and referral services. Findings suggest that most visitors surveyed had positive experiences, and more can be done to promote the Action Center and the variety of services it offers.